Study of Surface Potential and Electric Stress on Traction Insulators - Madhulita, Monali (2016)
Optimal performance of traction insulators is essential to ensure reliability of railway traction electrification system. They are exposed to environmental degradation and vandalism due to the overhead erection in railway lines. The likely damages that can take place are cracks in the sheds, or shorting of sheds due to formation of conducting dust and moisture layer on the surface. Fault in one shed increases the stress on the healthy sheds, resulting in an undesirable deviation of the electric field and potential profiles of the insulator from the normal ones, which may also lead to a flashover across the healthy portions. Surface charge simulation method (SCSM) is used to find the potential and electric field for the most widely used traction insulators in the country, and the stress increment is studied. The simulation results obtained for both healthy and fault-imposed insulators are presented, The experimental results of dry and wet withstand tests are presented along with the leakage current performance for the traction insulators.